The Effect of Couple Card Media on Elementary School Students’ Science Learning Outcomes in Class IV MIN 8 Medan City - Indi Rahmawati; Safran Safran (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The reason for conducting research is based on several problems in the form of teaching activities whose center is still on the teacher (teacher centered), on the other hand the students' learning outcomes are still low and the teaching process has not been able to fully improve student outcomes in their learning. The aim of the research is to find out the effect of Couple Card media on Elementary School Students’ Science Learning Outcomes in Class IV MIN 8 Medan City. The research method used was in the form of an experiment through a quasi-experimental design in the form of a nonequivalent control group, which acted as research subjects, consisting of 40 students of class IV. In analyzing the data, the researcher conducted a normality test accompanied by the Wilcoxon test due to not normally data distribution. Based on the Wilcoxon signed rank results, it can be seen that Asymp.Sig.(2-tailed) has a value of 0.001. Because the value of 0.000 is smaller than 0.05 (0.000 < 0.05) it is understood that there are differences in learning outcomes with these differences being significant both in the pretest and post-test when learning is not carried out using couple card media. Through the use of media in the form of couple cards it is known that there is an influence on the learning outcomes passed by students so that it was concluded that the media in the form of couple cards provided an increase in student results in their learning.